Increasing the generalizability of psychology by including Africans - (:unkn) unknown (My University, 2024)
African psychology is unknown globally, and psychology’s push for “big team science”, collaborative projects in which geographically dispersed collaborators pool together resources to accomplish huge projects, has failed to include Africans. To address these issues, we conducted two big team science replication projects focused on Africa. The first was pedagogically focused and concerned moral reasoning. We found that, consistent with the original US study, Africans from five countries were more sensitive to violation severity for harm violations than purity ones. This study also prepared our African collaborators for our second study, in which our African collaborators selected and later replicated 18 African-discovered claims about sexual behavior. Across sites in Africa, as well as Europe and North America, only 5 of these claims replicated successfully. This thesis improves Africans’ capacity in open science and foregrounds African psychology scholarship on the global stage.
Keywords: African Research